Modelling Socio - Digital Customer Relationship Management in the Hospitality Sector During the Pandemic Time - Mahmoud, Ali B.; Berman, Alenxander; Tehseen, Shehnaz *; Hack-Polay, Dieu (IGI Global, 2022)
The chapter builds on previous research and offers an updated theoretical model to determine the relationships among social media technologies, customer experience flow, customer relationship management, brand loyalty, word of mouth, firm performance, and customer engagement across a set of moderators in pandemic time. In line with the literature, customer engagement serves as a mediator that fully translates the effects of social media technology, customer flow experience and customer relationship management into positive levels of brand loyalty, word of mouth and firm performance. However, all of the relationships conceptualized in the model are hypothesized to be moderated by COVID-19 developments and perceptions.